Researching Neoliberal Reforms in Child Protection Agencies: A Quest for the New Century - Ann Reich (Adult Education Research Conference, 2000)
This study highlights the usefulness of a different mode of analysis to foreground the connections between neoliberal reforms in education and training and public sector organisations, and the practices of new technologies of training – in this case the "learning organisation."